2000
DOI: 10.1063/1.1331091
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient 2% Nd:yttrium aluminum garnet ceramic laser

Abstract: A highly efficient diode-laser end-pumped polycrystalline 2% Nd:yttrium aluminum garnet (YAG) ceramics laser that is comparable in efficiency with Nd:YAG single crystal laser has been developed. With 883 mW pumping, 465-mW-cw laser output at 1064 nm has been obtained corresponding to an optical-to-optical efficiency of 52.7%. The laser threshold is only 30 mW with R=97% output coupler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
88
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(93 citation statements)
references
References 5 publications
2
88
3
Order By: Relevance
“…8 Recently, authors reported on the fabrication of near surface channel waveguides in Nd:YAG ceramics.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 Recently, authors reported on the fabrication of near surface channel waveguides in Nd:YAG ceramics.…”
mentioning
confidence: 99%
“…7 As a matter of fact, the laser performance of Nd:YAG ceramics has been found to be equal or even superior to that corresponding to Nd:YAG crystals. 8 Recently, authors reported on the fabrication of near surface channel waveguides in Nd:YAG ceramics. 9 Nevertheless, up to date no attempt has been made, to the best of our knowledge, for the fabrication of buried channel waveguides in Nd:YAG ceramics by femtosecond DLW.…”
mentioning
confidence: 99%
“…Systematic studies of Nd:YAG ceramic lasers for different doping levels showed that if we dope Nd 3+ -ions highly, it is difficult to keep the large grain size and the number of grain boundaries will increase within the same path length accordingly (Ikesue et al, 1995 a, b;Shoji et al, 2000;Lu et al, 2000). In this section, our experimental results concerning lasing pattern formations due to grain boundaries and the resultant dynamic instabilities observed in Nd:YAG ceramic lasers (Kawai et al, 2004;Narita et al, 2005;Otsuka et al, 2006) are reviewed.…”
Section: Formation Of Local Transverse Modes and Associated Dynamic Ementioning
confidence: 99%
“…Over the years several efficient CW laser diode (LD) pumped lasers (e.g. see [10] [12,13]. Since the sintering temperature is about 600 °C lower than the polymorphic transition temperature, it is easier to fabricate large-size Y 2 O 3 :Ln 3+ ceramics.…”
Section: Introductionmentioning
confidence: 99%